IMPLEMENTATION OF NANJING SWANSOFT-BASED CNC LATHE SIMULATION IN THE MANUFACTURING OF PAPER WEIGHT PRODUCTS - Apriyanto Apriyanto; Desmarita Leni; Muchlisinalahuddin Muchlisinalahuddin; Yuni Vadila; Asroful Abidin (Yayasan Education and Social Center, 2026)
The development of manufacturing technology demands mastery of precise and efficient CNC lathe machines, but direct practice is often hampered by limited facilities, operational costs, and the risk of programming errors. This study aims to implement CNC lathe simulation based on Nanjing Swansoft CNC Simulator (SSCNC) in the manufacture of paper weight products as a medium for program verification and learning. The research methods include product design, machining parameter calculation, CNC program preparation using G-Code and M-Code based on FANUC 0i-T control, and testing through two machining stages. The workpiece has an initial diameter of 50 mm and a length of 54 mm with a chuck exit length of 40 mm at each stage. The cutting parameters used are a spindle speed of 1000 rpm and a feed rate of 0.5 mm/rev with an absolute programming system (G90). The tool configuration consists of a VNMG 350 carbide turning tool, an Ø18 mm drill, and a 2 mm internal grooving tool. The simulation results show that the two-stage program can be run without syntax errors, interpolation alarms, or tool path conflicts. The G02/G03 circular interpolation successfully generated a continuous radius, and all geometric features were formed according to the working drawings. The SSCNC simulation proved effective as a safe technical verification and learning medium before practicing on a real CNC machine.